Gravitational capture and maintenance of a spacecraft around pluto - Sanchez, Diogo M.; Prado, Antonio F.B.A.; Yokoyama, Tadashi [UNESP] (American Institute of Aeronautics and Astronautics (AIAA), 2014)
In this work, we study gravitational captures of a spacecraft by the Pluto-Charon system, searching configurations where the loss of energy of the spacecraft to Pluto is maximized in a time interval that keeps the viability of the mission, using the three-dimensional restricted three-body problem, taking into account the perturbation of the Pluto and Charon gravitational potentials (J2 and J22), the perturbation of the Sun and the gravity of the minor satellites of Pluto (Styx, Nix, Kerberos, and Hydra). The initial conditions which lead to captures of probes that remain in orbit around Pluto for 10 years or more will be considered as stable regions. During the gravitational capture maneuvers, some aspects will be measured in order to find the best maneuver, like the minimum energy after the capture and time consumed during the process. Those variables are important in the transfer orbit selection for this phase of the mission. Using the technique of the integral of the perturbing forces, we calculate the total velocity variation received by the spacecraft, in the stable regions, due to the Sun, Charon, the small satellites of Pluto and the J2 and J22 terms of the potential of Pluto and Charon. By the comparison between the velocity contribution of each disturber term and a Keplerian orbit around Pluto, we will be able to define which one of the disturbers are more significant, in order to make a decision about which forces need to be included in a model for a given accuracy and nominal orbit. We also will be able to find orbits that are less perturbed, requiring less station keeping maneuvers, and consequently orbits with good chances to become useful for a real mission, since these orbits come from captures.